2002
DOI: 10.1080/027868202753571241
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Particle Size Distributions due to Turbulent and Brownian Coagulation

Abstract: The time evolution of particle size distribution due to Brownian and turbulent coagulation (using the kernel of Kruis and Kusters (1997)) was systematically investigated. Using a new de nition of dimensionless size distribution parameters based on the geometric mean values, self-preserving particle size distributions for turbulent coagulation were found to exist. The width of such distributions depends on the initial size distribution as well as the turbulence intensity. When starting with submicron aerosols, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…At this point, turbulent coagulation can completely dominate Brownian coagulation (the Brownian coagulation kernel decreases with particle size as diameter to the minus 2 power; see, e.g., Seinfeld 1986). Turbulent coagulation is an extremely complex phenomenon that has recently received a lot of attention (Sundaram and Collins 1997;Reade and Collins 1998;Zhou, Wexler, and Wang 1998;Zhou 1998a, 1998b;Reade and Collins 2000;Park, Kruis, Lee, and Fissan 2002). We refer to the point where turbulent coagulation dominates Brownian coagulation as Region III.…”
Section: Introductionmentioning
confidence: 99%
“…At this point, turbulent coagulation can completely dominate Brownian coagulation (the Brownian coagulation kernel decreases with particle size as diameter to the minus 2 power; see, e.g., Seinfeld 1986). Turbulent coagulation is an extremely complex phenomenon that has recently received a lot of attention (Sundaram and Collins 1997;Reade and Collins 1998;Zhou, Wexler, and Wang 1998;Zhou 1998a, 1998b;Reade and Collins 2000;Park, Kruis, Lee, and Fissan 2002). We refer to the point where turbulent coagulation dominates Brownian coagulation as Region III.…”
Section: Introductionmentioning
confidence: 99%
“…This is gelation. Similarly to the acceleration component of the K (Kruis & Kusters, 1997;Park et al, 2002), the S a also increases with increasing particle size ratio, as the response to fluid velocity fluctuations (the difference in relaxation time) depends on that size ratio. Once large particles are formed, they essentially (1)): Evolutions of the (a) volume fraction distribution over relative particle diameter and (b) volume-based geometric standard deviation over particle residence time for various initial standard-deviations, gn,0 and initial number mean diameter d nm,0 = 100 nm.…”
Section: Dynamics Of Size Distribution In the Viscous Regime (D P > )mentioning
confidence: 92%
“…Combined Brownian and shear-induced coagulation can lead to self-preserving size distributions provided that shear rate decreases with time at a special rate (Wang & Friedlander, 1967). Park, Kruis, Lee, and Fissan (2002) found that accounting for the shear and acceleration components of turbulent coagulation in the viscous regime (d p > ) leads to asymptotic distributions that were not self-preserving, however, as they depended on the initial form of the distribution and eddy dissipation energy. An overview of the asymptotic behavior of various coagulation rates was given recently by Leyvraz (2003).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The distance where particle coagulation was apparent and the half-time, which is a crucial indicator in evaluating the degree of particle coagulation, was compared between the study and other researches. Most researchers have focused on particle coagulation in a steadystate environment in which particle dispersion did not occur (Park et al 2002;Kim et al 2003). However, the study examined particle coagulation during the process of dispersion, and a particle dispersion and a coagulation model were combined to determine how the two processes influenced each other.…”
Section: Introductionmentioning
confidence: 99%